KEPEMIMPINAN ADAPTIF KEPALA MADRASAH DALAM MENGEMBANGKAN KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM PADA ERA SOCIETY 5.0 - Khofifah; Ayu Daniyah Putri; Ansori (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2026)
his study aims to analyze the adaptive leadership of madrasah principals in developing the competencies of Islamic Religious Education (PAI) teachers in the Society 5.0 era and identify supporting and inhibiting factors in its implementation at MI At-Taqwa Bondowoso. The study used a qualitative approach with a case study type. Data were obtained from five key informants, namely the madrasah principal and four PAI teachers. Data collection was conducted through observation, interviews, and documentation for three days, namely on January 19–21, 2026. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña which includes data reduction, data presentation, and drawing conclusions, and their validity was tested through triangulation of sources and methods. The results of the study indicate that the adaptive leadership of madrasah principals is realized through technology-based supervision, digital training, strengthening digital literacy, and building a collaborative work culture that supports the development of PAI teacher competencies. The successful implementation of adaptive leadership is supported by the commitment of madrasah principals, teacher motivation, collaborative culture, and the availability of technological facilities. Inhibiting factors include limited digital infrastructure, differences in technological capabilities between teachers, and resistance to change. This research confirms that adaptive leadership is a crucial strategy for developing Islamic religious education teacher competencies and supporting the transformation of Islamic education in the Society 5.0 era.